(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In a sub chronic dietary pretreatment protocol chlordecone (CD) is a powerful potentiator of CCl4 hepatotoxicity, as indicated by biochemical, hepatofunctional, histopathological, and lethality parameters. The purpose of this investigation is to further explore the CD + CCl4 interaction in an acute CD pretreatment protocol and to compare the two pretreatment protocols in terms of their effect upon quantitative histopathology, serum enzymes, and lethality. Groups of four male rats received one of the following four pretreatments chlordecone (10 mgkg single po), mirex (10 mgkg single po), phenobarbital (PB) (80 mgkgday for 2 successive days ip in 0.9 saline), or corn oil vehicle (1 mlkg single po). Twenty-four hours later, the rats were given a single ip injection of CCl4 (0.1 mlkg). Twenty-four hours after CCl4 administration, serum enzymes (SGPT, SGOT, and ICD) were measured and the livers removed and fixed in 10 buffered formalin for histological evaluation. The LD50 were determined by the method of moving averages. CD + CCl4 was the most hepatotoxic combination, in terms of serum enzyme elevations and lethality followed by PB + CCl4. The PB + CCl4 combination caused a greater degree of hepatocyte necrosis. These findings indicate that the acute pretreatment with CD enhances hepatotoxicity and the lethality of CCl4 in a fashion qualitatively similar to the subchronic pretreatment protocol.